Market Illiquidity Premium on Stock Returns: An Empirical Study of Taiwan Stock Markets - Chen, Chia-Cheng; Tai, Chia-Li; Cho, Yi-Chun (Asian Economic and Financial Review, 2019)
This paper examined the existence of illiquidity premiums in Taiwan stock markets during 1982-2016. First, the illiquidity premium was calculated with the method of Amihud (2014) in a whole period and its three sub periods, and then a five-factor model was formed by adding the new risk premium to the traditional Fama-French-Carhart four-factor model. Then quint portfolios the illiquidity measure by Amihud (2002) in an ascending order and applies factor models to explore the relationship between stock returns and illiquidity premium. The empirical results indicated that the five-factor model increased the relative explanatory power compared to the traditional four-factor model. For the higher illiquidity portfolios, the illiquidity premium demonstrated significantly positive effects on stock returns and the five-factor model showed relatively smaller alphas, which in turn proved the existence of market illiquidity premiums. The empirical results are expected to enhance the understanding of the functioning of illiquidity on developed markets in the literature, and also add more evidence on the emerging market settings.